Mechanisms of Rumination Deactivation: An Interpretive Phenomenological Study in Young Adults with Anxiety - Nur , Jefri; Azzahranisa , Nafesa; Akhni , Okta Nurika (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to explore the lived experiences and underlying psychological and contextual mechanisms by which young adults with anxiety naturally deactivate rumination. Methods and Materials: A qualitative research design based on interpretive phenomenological analysis (IPA) was employed to gain an in-depth understanding of participants’ experiences. The study involved 21 Indonesian young adults (aged 18–30) who self-identified as experiencing recurrent anxiety and ruminative thought patterns. Participants were recruited through purposeful sampling from mental health support networks and university counseling centers. Data were collected through in-depth semi-structured interviews conducted in Bahasa Indonesia and analyzed using NVivo 14 software. Interviews continued until theoretical saturation was reached. Analysis followed iterative coding, theme development, and integration processes, with peer debriefing and member checking to ensure credibility and confirmability. Findings: Four overarching themes emerged: (1) awareness and cognitive shifts, including recognition of mental loops, decentering, cognitive reframing, and acceptance of imperfection; (2) emotional processing and release, such as naming core emotions, expressive disclosure, self-soothing practices, and emotional reappraisal; (3) behavioral and environmental regulation, encompassing structured routines, purposeful engagement, digital boundaries, and adaptive social connection; and (4) coping resources and growth, involving self-directed use of therapy-informed tools, spirituality and existential meaning-making, strengthening self-efficacy, and future-oriented hope. These mechanisms revealed a layered, dynamic process of disengaging from repetitive negative thinking in everyday contexts. Conclusion: Rumination deactivation among young adults with anxiety involves a synergistic interplay of metacognitive awareness, emotional regulation, behavioral structuring, and personal growth resources. Understanding these naturalistic strategies can inform culturally sensitive interventions, prevention programs, and self-help tools to support mental well-being in emerging adulthood.